Pengembangan Nilai Pendidikan Karakter Berbasis Profil Pelajar Pancasila Melalui Permainan Kotak Dolananku Pada Anak - Iswantiningtyas, Veny; Widi Wulansari; Rosa Imani Khan; Yunita Dwi Pristiani; Nursalim; Yolanda Titis Sofwina (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The child's attitude of not wanting to cooperate with friends to play together and the lack of group activities causes the child's cooperative character values less developed, resulting in an attitude of not caring about friends. Instilling the value of character education plays a vital role in supporting the Pancasila student profile program. This research explores the role of the Dolananku box game in strengthening the character values of cooperation and creativity based on the Pancasila student profile in early childhood. The type of research used is quasi-experimental. The research subjects were 62 children aged 5-6 years. Data collection techniques use tests and observations, while data analysis techniques use the Wilcoxon and Independent t-test. The research results show that applying the Dolananku box game has significantly strengthened children's cooperative and creative character values. The research concludes that there is an increase in the strengthening of cooperation and creative character values after being taught using the Dolananku box game compared to the abilities of children who were not given the Dolananku box game. The research implies a change in the value of cooperation, shown in the behavior of working together to assemble blocks into a work, and children can string beads.